Saudi Moumouvirus, the First Group B Mimivirus Isolated from Asia - Bajrai, Leena H.; de Assis, Felipe L.; Azhar, Esam I.; Jardot, Priscilla; Robert, Catherine; Abrahão, Jônatas; Raoult, Didier; La Scola, Bernard (Frontiers in Microbiology, 2016)
The number of novel giant viruses identified and characterized from the recently proposed order Megavirales has increased in recent years and new questions have been raised regarding viral diversity and evolution. Here, we describe the isolation and characterization of Saudi moumouvirus (SDMV), a new giant virus belonging to Mimivirus lineage B, isolated from a sewage sample taken from the King Abdulaziz University hospital in Jeddah, Saudi Arabia. SDMV presented 500 nm icosahedral particles with a 1,046,087 bp genome, which is larger than moumouvirus-like genomes which have been described in the past. The SDMV genome was predicted to encode 868 ORFs, ranging in size from 54 to 2,914 amino acids, with a mean size of 349 aa. Furthermore, this genome was predicted to encode 40 new genes (ORFans) without similarity with other sequences (ORFan L850 transcript was detected by qPCR in infected amoeba), in addition to 42 hypothetical proteins (pseudo-ORFs) with less than 100 aa, which matched other sequences in the NCBI nr database. Phylogenetic analysis showed that SDMV clustered together with mimiviruses from lineage B, including moumouvirus-like strains. It is, therefore, the 3rd Mimivirus to be isolated in Asia and the first of group B.